Dilema Teologi Mengenai Tantangan Dan Penerapan Misi Di Indonesia - Mulya, Fadilla (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2024)
Based on the Great Commission in Matthew 28:19-20, which commands Christians to spread the Gospel to all nations, this study explores the theological and ethical dilemmas faced by Christians in Indonesia. While the mission is a divine command, challenges arise when spreading the Good News in a pluralistic society, where religious freedom and interfaith harmony must be preserved. Through a qualitative approach involving interviews, observations, and document analysis, this paper highlights the importance of contextualizing the mission by respecting local values and upholding the principles of love and interfaith dialogue. This article also offers recommendations for the Church in Indonesia to carry out its mission wisely, with a focus on social service and promoting harmony in a pluralistic society.